The Effectiveness of Mozart Classical Music Therapy to Overcome Pain in Osteosarcoma Pedis Dextra Post-Amputation Surgery in the Darmawan Pavilion Treatment Room, 6th Floor, Gatot Soebroto Army Hospital - Yusuf, Bahreni; Rahmadani, Khansa Asilla (Akademi Keperawatan RSPAD Gatot Soebroto, 2022)
Pain is one of the problems that can occur in post-osteosarcoma amputation surgery. Music therapy is one of the therapy programs that is useful for reducing pain levels. This study aims to determine the effectiveness of classical Mozart music therapy on reducing pain levels in post-osteosarcoma amputation surgery patients. This study uses a descriptive research method in the form of a case study in post-osteosarcoma amputation surgery patients. Classical Mozart music therapy was given for ± 15 minutes in 3 meetings. The results of the study showed that there was a decrease in pain levels from a pain scale of 4 (moderate pain) to a pain scale of 1 (mild pain) after being given classical Mozart music therapy. The conclusion obtained is that classical Mozart music therapy is effective in reducing pain levels in post-osteosarcoma amputation surgery patients at RSPAD Gatot Soebroto.